2012
DOI: 10.1111/j.1365-4632.2011.05112.x
|View full text |Cite
|
Sign up to set email alerts
|

Scientific productivity of OECD countries in dermatology journals within the last 10‐year period

Abstract: Nearly half of all publications were performed by the European origin OECD countries, and one-third of all publications were performed by USA. Journals from Germany and France, which are published in their own language, receive fewer citations, but they contribute a lot to these countries with respect to the number of publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
2
15
0
1
Order By: Relevance
“…It has been reported that the number of publications in dermatology has been increasing year by year. 13,14 In the present study, we demonstrate that there has also been a dramatic increase in the number of publications in dermatology in mainland China. The dramatic increase in publications in mainland China could be partially attributable to its rapid economic growth.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…It has been reported that the number of publications in dermatology has been increasing year by year. 13,14 In the present study, we demonstrate that there has also been a dramatic increase in the number of publications in dermatology in mainland China. The dramatic increase in publications in mainland China could be partially attributable to its rapid economic growth.…”
Section: Discussionsupporting
confidence: 59%
“…16 Thus, the remarkable increase in publications is likely an economically driven phenomenon reflecting the rapid economic development in mainland China. In contrast, the annual growth rates of dermatological publications in mainland China were far more than the annual growth rates in dermatology in Economic Co-operation and Development countries (increased 50% in 10 years) 14 and other fields (2.2-9.9%) 17 in other regions of the world. Manpower is another determinant affecting the number of publications.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the area of research it becomes evident that many German departments of dermatology, especially due to the amount of basic research, lie in the upper range of the medical faculties. This underscores the previously published high level of performance of dermatologic research in Germany even in the international comparison [14–16].…”
Section: Discussionsupporting
confidence: 62%
“…[2][3][4][5] Studies on dermatological literature have been conducted in central European, Nordic and Organisation for Economic Cooperation and Development countries. [6][7][8] However, no global, long-term bibliometric studies have so far been conducted in this field.…”
mentioning
confidence: 99%